Fundamental Roles of the Golgi-Associated Toxoplasma Aspartyl Protease, ASP5, at the Host-Parasite Interface - Hammoudi, Pierre-Mehdi; Jacot, Damien; Mueller, Christina; Di Cristina, Manlio; Dogga, Sunil Kumar; Marq, Jean-Baptiste; Romano, Julia; Tosetti, Nicolò; Dubrot, Juan; Emre, Yalin; Lunghi, Matteo; Coppens, Isabelle; et al. (PLoS pathogens, 2015)
Toxoplasma gondii possesses sets of dense granule proteins (GRAs) that either assemble at, or cross the parasitophorous vacuole membrane (PVM) and exhibit motifs resembling the HT/PEXEL previously identified in a repertoire of exported Plasmodium proteins. Within Plasmodium spp., cleavage of the HT/PEXEL motif by the endoplasmic reticulum-resident protease Plasmepsin V precedes trafficking to and export across the PVM of proteins involved in pathogenicity and host cell remodelling. Here, we have functionally characterized the T. gondii aspartyl protease 5 (ASP5), a Golgi-resident protease that is phylogenetically related to Plasmepsin V. We show that deletion of ASP5 causes a significant loss in parasite fitness in vitro and an altered virulence in vivo. Furthermore, we reveal that ASP5 is necessary for the cleavage of GRA16, GRA19 and GRA20 at the PEXEL-like motif. In the absence of ASP5, the intravacuolar nanotubular network disappears and several GRAs fail to localize to the PVM, while GRA16 and GRA24, both known to be targeted to the host cell nucleus, are retained within the vacuolar space. Additionally, hypermigration of dendritic cells and bradyzoite cyst wall formation are impaired, critically impacting on parasite dissemination and persistence. Overall, the absence of ASP5 dramatically compromises the parasite's ability to modulate host signalling pathways and immune responses.
Keywords: fluorescenční protilátková technika; transport proteinů; Humans; toxoplazmóza; genový knockout; Protein Transport; Molecular Sequence Data; molekulární sekvence - údaje; Toxoplasmosis; Host-Parasite Interactions; Blotting, Western; ELISA; lidé; Gene Knockout Techniques; zvířata; myši; Cells, Cultured; myši inbrední C57BL; Enzyme-Linked Immunosorbent Assay; Mice; transfekce; Toxoplasma; Golgi Apparatus; Golgiho aparát; kultivované buňky; Mice, Inbred C57BL; Aspartic Acid Proteases; transmisní elektronová mikroskopie; Real-Time Polymerase Chain Reaction; Microscopy, Electron, Transmission; Transfection; Fluorescent Antibody Technique; Animals; western blotting; interakce hostitele a parazita; aspartátové proteasy; kvantitativní polymerázová řetězová reakce